Why are Children Still Out of School?: a Case Study of Urban Slums in Dehradun. - Bahuguna, Abhilasha and Gurmail Singh (2010)
This paper describes the socio-economic determinants of school dropout in Dehradun city’s slums with the aid of a household survey. The objectives were to establish household socio-economic factors that influence school dropout of pupils, despite various incentives such as free education, uniform, scholarships, books and midday meals under ‘Pahal’, an initiative of Sarva Shiksha Abhiyan in Uttarakhand for providing school education to urban, deprived, out-of-school children (6-14 years), such as rag pickers, scavengers and street beggars.